Perubahan Pola Bahasa dalam Komunikasi Digital Remaja: Kajian Kualitatif Linguistik, Sosiologi, dan Teknologi Informasi - Raudhatul Jannah; Eka Saryanti; Dyah Adilla Perdana (Sociale : Journal of Social Science, 2026)
This study aims to analyze changes in language patterns in adolescents' digital communication using a qualitative approach that combines linguistic, sociological, and information technology perspectives. The transformation of language patterns in the digital space has become increasingly significant with the increasing intensity of use of platforms such as WhatsApp, Instagram, and TikTok in adolescents' daily lives. Research data was obtained through observations of digital communication in online chat groups and documentation of conversation screenshots, which were analyzed thematically using a linguistic and social interpretation framework. The results show that adolescents develop new language patterns characterized by shortening words, using creative abbreviations, mixing Indonesian and English, and integrating visual symbols such as emojis and stickers as part of the message structure. From a sociological perspective, these language patterns function as group identity and a means of building social closeness in digital communities. Meanwhile, digital platform features such as auto-suggestion, recommendation algorithms, and the ease of use of stickers have been shown to influence adolescents' language choices and communication expressions. These findings confirm that language changes in digital communication are not random but are shaped by the interaction between linguistic factors, social dynamics, and technological influences.